215k views
4 votes
PLZZZZZZ can someone help me out with this and explain !

PLZZZZZZ can someone help me out with this and explain !-example-1

2 Answers

5 votes

Answer:

D. x² - 3x + 1

Explanation:

let

f(x) = x² + 1

g(x) = 3x

find: f-g

f-g = f9x) - g(x)

= x² + 1 - 3x

= x² - 3x + 1

therefore, D is the answer

User Joevallender
by
5.0k points
0 votes
Here you go!! Hope it helps
PLZZZZZZ can someone help me out with this and explain !-example-1
User Cwa
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.